2013
DOI: 10.1002/qua.24427
|View full text |Cite
|
Sign up to set email alerts
|

Nature of closed‐ and open‐shell interactions between noble metals and rare gas atoms

Abstract: Interactions between noble metals and rare gases have become an interesting topic over the last few years. In this work, a computational study of the open-shell (d 10 s 1 ) and closed-shell (d 10 s and d 10 s 2 ) noble metals (M ¼ Cu, Ag, and Au) with three heaviest rare gas atoms (Rg ¼ Kr, Xe, and Rn) has been performed. Potential energy curves based on ab initio [MP2, MP4, QCISD, and CCSD(T)] and DFT functionals (M06-2X and CAM-B3LYP) were obtained for ionic and neutral AuXe complexes. Dissociation energies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 76 publications
(76 reference statements)
1
28
0
2
Order By: Relevance
“…Thei nvestigation of closed-shell interactions between Au + and Ng atoms began somewhat earlier, [6][7][8] and is still the subject of numerous studies, [9][10][11][12] although Au + ÀNg complexes are putatively simple two-atom systems.V arious effects,from dispersion forces and charge-induced dipole interactions up to even ad egree of covalency, play an important role in the description of their interesting chemical bonding.I nt he 1990s,Pyykkç suggested an increased covalencyofthe Au + À Ng interaction as the Ng changes from He to Xe,b ased on ar emarkable charge transfer from Xe to Au + formally indicating ac hemical bond. [6] This proposed increased covalencyw as questioned and attributed instead to longrange polarization and dispersion effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thei nvestigation of closed-shell interactions between Au + and Ng atoms began somewhat earlier, [6][7][8] and is still the subject of numerous studies, [9][10][11][12] although Au + ÀNg complexes are putatively simple two-atom systems.V arious effects,from dispersion forces and charge-induced dipole interactions up to even ad egree of covalency, play an important role in the description of their interesting chemical bonding.I nt he 1990s,Pyykkç suggested an increased covalencyofthe Au + À Ng interaction as the Ng changes from He to Xe,b ased on ar emarkable charge transfer from Xe to Au + formally indicating ac hemical bond. [6] This proposed increased covalencyw as questioned and attributed instead to longrange polarization and dispersion effects.…”
mentioning
confidence: 99%
“…[10,14] All-electron Dirac-Coulomb CCSD-(T) calculations in the relativistic four-component framework indicate the formation of polar covalent bonds in Au + À Ng complexes,s upporting these suggestions. [11] Another recent CCSD(T) and DFT bond analysis of MÀNg (M = Cu, Ag, Au ; Ng = Kr,X e, Rn) complexes of different charge states also revealed that in cationic Au + À Ng complexes,b oth electrostatic and covalent interactions are responsible for the bond strength, [12] while the bonds in anionic and neutral species are of pure electrostatic nature.T he results of this study can be explained by relativistic bond length contractions owing to stabilization of sand pshells and destabilization of the dand f shells.T hese previous and recent studies,h owever, point to the still-open questions about this unusually strong closedshell interaction of the d 10 Au + ion with aNga tom. [8] To gain further insight into this problem, mixed trimeric clusters of gold and silver can serve as ideal model systems.…”
mentioning
confidence: 99%
“…Herein, the number of active sites and moreover the maximum number of Rg atoms that interact with Ag 4 (D 2h ) and Ag 6 (D 3h ) clusters are 2 and 3 atoms, respectively. Cationic noble metal cluster has a significant affinity for interactions with Rg atoms in comparison to the neutral metal cluster, therefore, the complexation of cationic odd atom metal clusters, Ag3,5+, have been considered to find out the effect of increasing binding energies in the perturbation of IR and Raman spectra. The stable planar cationic clusters were selected and their interactions with one Rg atom have been considered.…”
Section: Resultsmentioning
confidence: 99%
“…In line with this, Cappelletti et al [39] have stated the ''birth of the hydrogen bond'' between water and some rare gases, Barreto et al. [40] described van der Waals forces in complexes of water and peroxides with rare gases, whereas Jamshidi et al [41] have asserted that metals and rare gases bind to each other in a stable form. Although the existence of protonated rare gas clusters is known [42], the main goal of the current work is focused on a quantum chemical study of intermolecular interactions between rare gases, such as argon, helium, krypton, or neon, and the ethyl cation (C 2 H 5 + ), whose HÁÁÁAr, HÁÁÁHe, HÁÁÁKr, and HÁÁÁNe contacts will be examined by means of structural investigation, determination of electronic parameters, infrared spectroscopy analysis, topological integrations of charge densities, and molecular orbital calculations.…”
Section: Introductionmentioning
confidence: 91%